Synthesis of unsymmetrical monocarbonyl curcumin analogues with potent inhibition on prostaglandin E2 production in LPS-induced murine and human macrophages cell lines - Mohd Aluwi, Mohd Fadhlizil Fasihi; Rullah, Kamal; Mohd Yamin, Bohari; Leong, Sze Wei; Abdul Bahari, Mohd Nazri; Lim, Sock Jin; Mohd Faudzi, Siti Munirah; Jalil, Juriyati; Abas, Faridah; Mohd Fauzi, Norsyahida; Ismail, Nor Hadiani; Jantan, Ibrahim; et al. (Elsevier, 2016)
The syntheses and bioactivities of symmetrical curcumin and its analogues have been the subject of interest by many medicinal chemists and pharmacologists over the years. To improve our understanding, we have synthesized a series of unsymmetrical monocarbonyl curcumin analogues and evaluated their effects on prostaglandin E2 production in lipopolysaccharide-induced RAW264.7 and U937 cells. Initially, compounds 8b and 8c exhibited strong inhibition on the production of PGE2 in both LPS-stimulated RAW264.7 (8b, IC50 = 12.01 μM and 8c, IC50 = 4.86 μM) and U937 (8b, IC50 = 3.44 μM and 8c, IC50 = 1.65 μM) cells. Placing vanillin at position Ar2 further improved the potency when both compounds 15a and 15b significantly lowered the PGE2 secretion level (RAW264.7: 15a, IC50 = 0.78 μM and 15b, IC50 = 1.9 μM while U937: 15a, IC50 = 0.95 μM and 15b, IC50 = 0.92 μM). Further experiment showed that compounds 8b, 8c, 15a and 15b did not target the activity of downstream inflammatory COX-2 mediator. Finally, docking simulation on protein targets COX-2, IKK-β, ERK, JNK2, p38α and p38β were performed using the conformation of 15a determined by single-crystal XRD.